The Canadian Bank Amendment Act of 1900 - Breckenridge, R. M. (Quarterly Journal of Economics, 1900)
The Canadian Bank Amendment Act of 1900 R. M. Breckenridge R. M. Breckenridge New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 4, August 1900, Pages 543–551, https://doi.org/10.2307/1883425 Published: 01 August 1900